2015
DOI: 10.1177/0898264315585503
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of Aging Long-Term Mexican American Heroin Injectors

Abstract: Objective To examine the applicability of the “maturing out” theory to a sample of aging Mexican American men who are long-term heroin injectors. Method Ethnographic data were collected as part of a cross-sectional study of aging Mexican American heroin users in Houston with 20 current heroin users. Results Findings indicate that dysfunctions that emerge in the heroin lifestyle lead not to cessation but rather to “maturing in,” a specific process of social readjustment that returns the heroin user to a sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 38 publications
0
14
1
Order By: Relevance
“…While prior work has found that older chronic users adapt their substance use, but remain immersed in it (Levy & Anderson; 2005; Anderson & Levy, 2003; Cepeda, Nowotony & Valdez, 2016), these data reveal that an involuntary period of sobriety may interrupt an addiction career, and set men on a new trajectory. Building on Best et al (2011), whose respondents in remission from heroin identified older age as an important turning point away from substance use, this research suggests that detoxification and sobriety experienced in prison may serve as an important “turning point” away from drug use for older men.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…While prior work has found that older chronic users adapt their substance use, but remain immersed in it (Levy & Anderson; 2005; Anderson & Levy, 2003; Cepeda, Nowotony & Valdez, 2016), these data reveal that an involuntary period of sobriety may interrupt an addiction career, and set men on a new trajectory. Building on Best et al (2011), whose respondents in remission from heroin identified older age as an important turning point away from substance use, this research suggests that detoxification and sobriety experienced in prison may serve as an important “turning point” away from drug use for older men.…”
Section: Discussionmentioning
confidence: 65%
“…Despite their increasing marginalization, authors conclude that older users are unlikely to “retire” from their chronic usage in the absence of illness or death. More recently in a study of Mexican-American long-term heroin injectors, Cepeda, Nowotony & Valdez (2016) show that older men, increasingly beset by “dysfunctional life changes” as a result of escalating substance use, did not “mature out” and enter a period of recovery, but rather “matured in” to a more stable or maintenance level of heroin use in older age, a use trajectory facilitated by the strong social support of families and social networks.…”
Section: Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Heroin has historically been consumed by Mexican Americans living in impoverished and economically and racially segregated neighborhoods in San Antonio (Desmond and Maddux, 1984; Valdez and Cepeda, 2008; Valdez et al, 2011). This context has given rise to a vibrant drug market, making marginalized and drug-using populations more susceptible to arrest, incarceration, and gang involvement (Cepeda et al, 2015; Valdez and Cepeda, 2008). …”
Section: 0 Materials and Methodsmentioning
confidence: 99%